Frommer's Colorado - Laine, Don. 4 0 16; 1973- Laine, Barbara.;Peterson, Eric; 5 (Hoboken, NJ : Wiley Publishing, Inc., 2007)
Presents guidance and tools for visitors to Colorado, including a foldout map, trip planning information, itineraries, lodging and dining suggestions for different budgets, and details on history, culture, and things to see and do.
Map on endpaper.;Includes a fold out map.;Includes index.
Adult;Adult
Keywords: 2 -- 0; 6; 20; Colorado;Colorado -- Guidebooks.;Guidebooks.; 2